CRITICAL ANALYSIS OF MEDICAL LABORATORY TECHNICIAN TRAINING PROGRAMS: EXAMINING CURRICULUM RELEVANCE, CLINICAL SKILLS DEVELOPMENT, AND ADHERENCE TO ACCREDITATION STANDARDS - Nashir Ali Alsagoor, Fatima Hamad Saad Al Ghamdi, Rakan Ahmad Al RAJAB, Moneer Husein Moslih Alaglah, Abdulmuti Saeed FaragAljohani, Abdullah Saleh Abdullah Al Amri, Abdulrahman Mohsen YahyaZabr (Chelonian Research Foundation, 2022)
Medical Technologist (MLT) Training Programs are at the heart of preparing students for a career in medicine and science involving laboratories. This article explores the critical components of MLT courses, such as guiding, the relevance of the syllabus, and following the accreditation standards. By gathering and presenting the main findings of the literature review and a source-to-source analysis, this paper intends to procure insights into the issues of strengths and weaknesses in MLT education and give proposals for areas that need further improvement. Keywords: medical laboratory technician, education, curriculum, and clinical skills are an index to identify accreditation standards.